Rancang Bangun Aplikasi Penilaian Berbasis Kurikulum 2013 (K13) Studi Kasus pada SMP Negeri 5 Sidoarjo - Yusuf Budiharjo; Bambang Hariadi; Vivine Nurcahyawati (Jurnal Sistem Informasi Universitas Dinamika, 2017)
The purpose of this research is to create applications that can perform the calculation and the conversion of the score of the range 10-100 into E-A automatically table with values already determined in accordance with the rules of the curriculum of 2013. The application can also draw up a blend of various assessments conducted by teachers of subjects, extracurricular teacher and homeroom teachers become student’s final reports. The making of the application, using the methods of the System Development Life Cycle (SDLC). Based on the results of the testing that was done, the application can be run as expected. The application can be developed into an integrated information system to generate more accurate data